Cinematic rendering to improve visualization of supplementary and ectopic teeth using CT datasets - Willershausen, Ines; Necker, Fabian; Kloeckner, Roman; Seidel, Corinna Lesley; Paulsen, Friedrich; Gölz, Lina; Scholz, Michael (Dentomaxillofacial Radiology, 2023)
OBJECTIVES: Ectopic, impacted, and supplementary teeth are the number one reason for cross-sectional imaging in pediatric dentistry. The accurate post-processing of acquired data sets is crucial to obtain precise, yet also intuitively understandable three-dimensional (3D) models, which facilitate clinical decision-making and improve treatment outcomes. Cinematic rendering (CR) is anovel visualization technique using physically based volume rendering to create photorealistic images from DICOM data. The aim of the present study was to tailor pre-existing CR reconstruction parameters for use in dental imaging with the example of the diagnostic 3D visualization of ectopic, impacted, and supplementary teeth. METHODS: CR was employed for the volumetric image visualization of midface CT data sets. Predefined reconstruction parameters were specifically modified to visualize the presented dental pathologies, dentulous jaw, and isolated teeth. The 3D spatial relationship of the teeth, as well as their structural relationship with the antagonizing dentition, could immediately be investigated and highlighted by separate, interactive 3D visualization after segmentation through windowing. RESULTS: To the best of our knowledge, CR has not been implemented for the visualization of supplementary and ectopic teeth segmented from the surrounding bone because the software has not yet provided appropriate customized reconstruction parameters for dental imaging. When employing our new, modified reconstruction parameters, its application presents a fast approach to obtain realistic visualizations of both dental and osseous structures. CONCLUSIONS: CR enables dentists and oral surgeons to gain an improved 3D understanding of anatomical structures, allowing for more intuitive treatment planning and patient communication.
CRIS-Team Scopus Importer:2023-05-05
Keywords: 3D visualization; CBCT; CT; dental anatomy; dental radiology; volume rendering

Congenital Nail Disorders among Children with Suspected Ectodermal Dysplasias - Maier-Wohlfart, Sigrun; Aicher, Carmen; Willershausen, Ines; Peschel, Nicolai; Meißner, Udo; Gölz, Lina; Schneider, Holm (Genes, 2022)
We report on a cohort of 204 children referred between January 2017 and January 2022 to the German Center for Ectodermal Dysplasias, Erlangen. The most frequent reasons for referral were tooth malformations and lack of multiple teeth leading to the suspicion of an ectodermal dysplasia. Many patients also suffered from being unable to perspire. Nail abnormalities, in contrast, represented a much rarer finding, albeit the impact on some individuals was large. As ectodermal dysplasias are congenital genetic conditions affecting the development and/or homeostasis of two or more ectodermal derivatives, including hair, teeth, nails, and certain glands, we analyzed congenital nail disorders detected in these patients. Dystrophic or otherwise abnormal nails were evident in 17 of 18 subjects with pathogenic WNT10A or GJB6 variants but in none of 161 children with EDA variants underlying X-linked hypohidrotic ectodermal dysplasia. However, 2 of 17 children who carry mutations in EDAR or EDARADD, two other genes involved in the ectodysplasin A signaling pathway, showed nail abnormalities, such as brittle or hypoplastic nails. TP63 variants were regularly associated with nail disorders. In one girl, anonychia congenita caused by a compound heterozygous variant of the R-spondin-4 gene (RSPO4) was diagnosed. Thus, nail dysplasia is rarer among patients with ectodermal dysplasia than commonly thought.
CRIS-Team Scopus Importer:2022-12-09
Keywords: anonychia/hyponychia congenita; congenital nail disorders; ectodermal dysplasia; R-spondin 4 (RSPO4)

Evaluating Cardiac Lateralization by MRI to Simplify Estimation of Cardiopulmonary Impairment in Pectus Excavatum - Abu-Tair, Tariq; Turial, Salmai; Willershausen, Ines; Alkassar, Muhannad; Staatz, Gundula; Kampmann, Christoph (Diagnostics, 2023)
Background: The severity of pectus excavatum is classified by the Haller Index (HI) and/or Correction Index (CI). These indices measure only the depth of the defect and, therefore, impede a precise estimation of the actual cardiopulmonary impairment. We aimed to evaluate the MRI-derived cardiac lateralization to improve the estimation of cardiopulmonary impairment in Pectus excavatum in connection with the Haller and Correction Indices. Methods: This retrospective cohort study included a total of 113 patients (mean age = 19.03 ± 7.8) with pectus excavatum, whose diagnosis was verified on cross-sectional MRI images using the HI and CI. For the development of an improved HI and CI index, the patients underwent cardiopulmonary exercise testing to assess the influence of the right ventricle’s position on cardiopulmonary impairment. The indexed lateral position of the pulmonary valve was utilized as a surrogate parameter for right ventricle localization. Results: In patients with PE, the heart’s lateralization significantly correlated with the severity of pectus excavatum (p ≤ 0.001). When modifying HI and CI for the individual’s pulmonary valve position, those indices are present with greater sensitivity and specificity regarding the maximum oxygen-pulse as a pathophysiological correlate of reduced cardiac function (χ2 10.986 and 15.862, respectively). Conclusion: The indexed lateral deviation of the pulmonary valve seems to be a valuable cofactor for HI and CI, allowing for an improved description of cardiopulmonary impairment in PE patients.
CRIS-Team Scopus Importer:2023-03-24
Keywords: cardiac lateralization; cardiopulmonary exercise testing; chest wall deformity; correction index; Haller index; pectus excavatum

Evaluation of hard palate and cleft morphology in neonates with Pierre Robin Sequence and Cleft Palate Only - Willershausen, Ines; Krautkremer, Nils; Ströbel, Armin; Abu-Tair, Tariq; Paulsen, Friedrich; Strobel, Karin; Kopp, Markus; May, Matthias; Uder, Michael; Krautkremer, Franziska; Gölz, Lina (Orthodontics & Craniofacial Research, 2024)
Objectives: This study aimed to establish a fully digital measurement protocol for standardizing the description of hard palate and cleft morphology in neonates with an isolated cleft palate (CPO) and Pierre Robin sequence (PRS). Materials and Methods: A total of 20 digitized plaster models of neonates with CPO and 20 digitized plaster models of neonates with PRS were retrospectively investigated. For the control group, the hard palate was segmented from 21 pre-existing 1.5 T MRI datasets of neonates and exported as an STL file. The digital models were marked with predefined reference points by three raters. Distance, angular, and area measurements were performed using Blender and MeshLab. Results: Neonates with CPO (20.20 ± 2.33 mm) and PRS (21.41 ± 1.81 mm) had a significantly shorter hard palate than the control group (23.44 ± 2.24 mm) (CPO vs. control: P <.001; PRS vs. control: P =.014). Notably, neonates with PRS (33.05 ± 1.95 mm) demonstrated a significantly wider intertuberosity distance than those with CPO (30.52 ± 2.28 mm) (P =.012). Furthermore, there were also significant differences measured between the cleft and control groups (25.22 ± 2.50 mm) (P <.001). Conclusions: The data from this study demonstrate the feasibility of using MRI datasets to generate digital models of the hard palate. The presence of a cleft palate leads to pronounced adaptations of the total palatal surface area, dorsal width, and length of the hard palate. Mandibular retrognathia and altered tongue position in PRS, as opposed to CPO, might further impact palatal morphology and intertuberosity distance.
CRIS-Team Scopus Importer:2024-05-31
Keywords: cleft palate only; digital orthodontics; MRI; paediatric radiology; Pierre Robin sequence

Feasibility of 3 Tesla MRI for the assessment of mid-palatal suture maturation: a retrospective pilot study - Willershausen, Ines; Kopp, Markus; Scholz, Michael; Ströbel, Armin; Seidel, Corinna Lesley; Paulsen, Friedrich; Uder, Michael; Gölz, Lina; May, Matthias (Odontology, 2024)
The maxilla occupies a key position in dentofacial orthopaedics, since its transversal development can be directly influenced by orthodontic therapy. The maturation stages of the mid-palatal suture, which are obtained from cone-beam computed tomography images (CBCT), present an addition to clinical decision-making in transversal discrepancies of the upper jaw. In an endeavour to reduce ionizing radiation in adolescents and young adults, who are particularly susceptible to long term stochastic irradiation effects, we investigated the feasibility of 3 Tesla (3T) MRI in detecting the maturation stages of the mid-palatal suture. A collective of 30 patients aged 24–93 years with routine neck MRI at 3T, underwent an additional three-dimensional isotropic T1 weighted study sequence of the midface. Image evaluation was performed on axial, multi-planar formatted reconstructions of the dataset aligned to the midline axis of the palate, and curved reconstructions aligned to the concavity of the palate. Inverted images helped to achieve an image impression similar to the well-known CBCT appearance. All datasets were reviewed by three readers and mid-palatal maturation was scored twice according to Angelieri et al. Intra- and inter-rater agreement were evaluated to measure the robustness of the images for clinical evaluation. 3T MRI deemed reliable for the assessment of mid-palatal suture maturation and hence for the appraisal of the hard palate and its adjacent sutures. The data of this pilot study display the feasibility of non-ionizing cross-sectional MRI for the determination of sutural maturation stages. These findings underline the potential of MRI for orthodontic treatment planning, further contributing to the avoidance of unnecessary radiation doses.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Anatomy; Mid-palatal suture; MRI; Orthodontics; Radiology

Halitosis in Oral and Maxillofacial Surgery Patients-a Pilot Study - Willershausen, Ines; Krautkremer, Franziska; Sagheb, Kawe; Weider, Matthias; Weusmann, Jens; Mittermeier, Fabienna; Erhard, Julia; Sagheb, Keyvan; Gölz, Lina; Walter, Christian (Clinical Laboratory, 2021)
Background: Halitosis is a relatively inhomogeneous pathology with an extremely high prevalence in the population. Potential risk factors for bad breath include bacterial decomposition of organic material as well as numerous general and systemic diseases. The aim of the present study was to analyze whether certain subgroups of oral and maxillofacial surgery patients have a higher risk of halitosis. Further the impact of halitosis on the patient's quality of life was ascertained.
CRIS-Team WoS Importer:2021-12-10

Impact of different cephalometric skeletal configurations on anatomic midface parameters in adults - Willershausen, Ines; Ehrenfried, Amelie; Krautkremer, Franziska; Ströbel, Armin; Seidel, Corinna Lesley; Paulsen, Friedrich; Kopp, Markus; Uder, Michael; Gölz, Lina; May, Matthias (Clinical Oral Investigations, 2024)
Objectives: Skull morphology and growth patterns are essential for orthodontic treatment, impacting clinical decision making. We aimed to determine the association of different cephalometric skeletal configurations on midface parameters as measured in 3D CT datasets. Materials and methods: After sample size calculation, a total of 240 fully dentulous patients between 20 and 79 years of age (mean age: 42 ± 15), who had received a CT of the skull within the scope of trauma diagnosis or intracranial bleeding, were retrospectively selected. On the basis of cephalometric analysis, using MPR reconstructions, patients were subdivided into three different vertical skull configurations (brachyfacial, mesofacial, dolichofacial) and the respective skeletal Class I, II, and III relationships. Anatomic parameters were measured using a three-dimensional post-processing console: the thickness of the maxillary and palatine bones as well as the alveolar crest, maxillary body and sutural length, width and height of the hard palate, maxillary facial wall thickness, and masseter muscle thickness and length. Results: Individuals with brachyfacial configurations had a significantly increased palatal and alveolar ridge thicknesses compared to those with dolichofacial- or mesofacial configurations. Brachyfacial configurations presented a significantly increased length and thickness of the masseter muscle (4.599 cm; 1.526 cm) than mesofacial (4.431 cm; 1.466 cm) and dolichofacial configurations (4.405 cm; 1.397 cm) (p < 0.001). Individuals with a skeletal Class III had a significantly shorter palatal length (5.313 cm) than those with Class I (5.406 cm) and Class II (5.404 cm) (p < 0.01). Sutural length was also significantly shorter in Class III (p < 0.05). Conclusions: Skeletal configurations have an impact on parameters of the bony skull. Also, measurable adaptations of the muscular phenotype could result. Clinical relevance: The association between viscerocranial morphology and midface anatomy might be beneficial for tailoring orthodontic appliances to individual anatomy and planning cortically anchored orthodontic appliances.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Anatomy; Cephalometry; Computed tomography; Midface; Orthodontics; Ultra-high-resolution datasets

Low-Field MRI for Dental Imaging in Pediatric Patients with Supernumerary and Ectopic Teeth: A Comparative Study of 0.55 T and Ultra-Low-Dose CT - Willershausen, Ines; Evangeliou, Stefania; Fautz, Hans Peter; Amarteifio, Patrick; May, Matthias; Ströbel, Armin; Zeilinger, Martin; Uder, Michael; Gölz, Lina; Kopp, Markus (Investigative Radiology, 2024)
Objectives This study sought to elucidate the diagnostic performance of 0.55 T magnetic resonance imaging (MRI) for pediatric dental imaging, specifically in terms of the image quality (IQ) for detecting ectopic and/or supernumerary teeth, compared with routine ultra-low-dose computed tomography (ULD-CT) of the jaw. Materials and Methods A total of 16 pediatric patients (mean age: 12.4 ± 2.6 years, range: 9-17 years) with ectopic and/or supernumerary teeth screened from January 2023 to January 2024 were enrolled in this prospective, single-center study. All patients underwent ULD-CT as the clinical reference standard and 0.55 T MRI as the study scan on the same day. A 0.6-mm isotropic 3-dimensional T1w FLASH sequence was developed with a dedicated field of view of the upper and lower jaws. ULD-CT was performed using a new single-source computed tomography (CT) scanner equipped with a tin filter (Sn100, slice thickness: 1 mm, quality reference mAs: 24). The IQ for the tooth axis, the tooth length, the tooth root, root resorptions, cysts, the periodontal ligament space, and the mandibular canal was evaluated twice by 3 senior readers using a 5-point Likert scale (LS) (LS score of 1: insufficient, 3: reduced IQ but sufficient for clinical use, and 5: perfect) and compared between both methods. Subsequently, the results were dichotomized into nonvalid (LS score of ≤2) and valid (LS score of ≥3) for clinical use. Results A total of 49 ectopic and/or supernumerary teeth in 16 pediatric patients were investigated using ULD-CT (CTDI: 0.43 ± 0.09 mGy) and 0.55 T MRI. The mean MRI acquisition time was 9:45 minutes. Motion artifacts were nonsignificantly different between 0.55 T MRI and ULD-CT (P = 0.126). The IQ for the tooth axis, the tooth root, root resorptions, and cysts was similar between the methods. The IQ for the periodontal ligament space and tooth length favored ULD-CT by 14% (confidence interval [CI]: 4.3%-24%) and 7.5% (CI: 1.8%-13%), respectively, whereas that for the mandibular canal favored 0.55 T MRI by -35% (CI: -54%-16%). Sufficient IQ was found especially for cystic lesions (CT: 100% sufficient, MRI: 95% sufficient), the tooth root (CT: 100%, MRI: 98%), root resorptions (CT: 94%; MRI: 85%), the tooth axis (CT: 100%; MRI: 98%), and the tooth length (CT: 99%; MRI: 91%). Conclusions The findings indicate that 0.55 T MRI is a feasible, radiation-free technique for delineating ectopic and/or supernumerary teeth in pediatric patients. Nevertheless, to date, 0.55 T MRI has not yet been able to provide an optimal IQ for all anatomical tooth and jaw structures. In cases of advanced clinical indications that require optimal spatial resolution, high-resolution CT or cone-beam CT may still be necessary.
CRIS-Team Scopus Importer:2024-11-22
Keywords: 0.55 T MRI; ectopic teeth; low-field MRI; orthodontics; pediatric radiology; ultra-low-dose CT

Orofacial clefts alter early life oral microbiome maturation towards higher levels of potentially pathogenic species: A prospective observational study - Seidel, Corinna Lesley; Strobel, Karin; Weider, Matthias; Tschaftari, Marco; Unertl, Christoph; Willershausen, Ines; Weber, Manuel; Hörning, André; Morhart, Patrick; Schneider, Michael; Beckmann, Matthias; Bogdan, Christian; et al. (Journal of Oral Microbiology, 2023)
Orofacial clefts (OFC) present different phenotypes with a postnatal challenge for oral microbiota development. In order to investigate the impact of OFC on oral microbiota, smear samples from 15 neonates with OFC and 17 neonates without OFC were collected from two oral niches (tongue, cheek) at two time points, i.e. after birth (T0: Ø3d OFC group; Ø2d control group) and 4–5 weeks later (T1: Ø32d OFC group; Ø31d control group). Subsequently, the samples were analyzed using next-generation sequencing. We detected a significant increase of alpha diversity and anaerobic and Gram-negative species from T0 to T1 in both groups. Further, we found that at T1 OFC neonates presented a significantly lower alpha diversity (lowest values for high cleft severity) and significantly higher levels of Enterobacteriaceae (Citrobacter, Enterobacter, Escherichia-Shigella, Klebsiella), Enterococcus, Bifidobacterium, Corynebacterium, Lactocaseibacillus, Staphylococcus, Acinetobacter and Lawsonella compared to controls. Notably, neonates with unilateral and bilateral cleft lip and palate (UCLP/BCLP) presented similarities in beta diversity and a mixture with skin microbiota. However, significant differences were seen in neonates with cleft palate only compared to UCLP/BCLP with higher levels of anaerobic species. Our findings revealed an influence of OFC as well as cleft phenotype and severity on postnatal oral microbiota maturation.
CRIS-Team Scopus Importer:2023-01-20
Keywords: early life dysbiosis; microbiome maturation; neonates; oral microbiome; Orofacial clefts

Orofacial clefts lead to increased pro-inflammatory cytokine levels on neonatal oral mucosa - Seidel, Corinna Lesley; Percivalle, Elena; Tschaftari, Marco; Weider, Matthias; Strobel, Karin; Willershausen, Ines; Unertl, Christoph; Schmetzer, Helga M.; Weber, Manuel; Schneider, Michael; Frey, Benjamin; Gaipl, Udo; et al. (Frontiers in Immunology, 2022)
Orofacial clefts (OFC) are frequent congenital malformations characterized by insufficient separation of oral and nasal cavities and require presurgical infant orthopedics and surgical interventions within the first year of life. Wound healing disorders and higher prevalence of gingivitis and plaque levels are well-known challenges in treatment of children with OFC. However, oral inflammatory mediators were not investigated after birth using non-invasive sampling methods so far. In order to investigate the impact of OFC on oral cytokine levels, we collected tongue smear samples from 15 neonates with OFC and 17 control neonates at two time points (T), T0 at first consultation after birth, and T1, 4 to 5 weeks later. The samples were analyzed using multiplex immunoassay. Overall, we found significantly increased cytokine levels (TNF, IL-1β/-2/-6/-8/-10) in tongue smear samples from neonates with OFC compared to controls, especially at T0. The increase was even more pronounced in neonates with a higher cleft severity. Further, we detected a significant positive correlation between cleft severity score and distinct pro-inflammatory mediators (GM-CSF, IL-1β, IL-6, IL-8) at T0. Further, we found that breast-milk (bottle) feeding was associated with lower levels of pro-inflammatory cytokines (IL-6/-8) in neonates with OFC compared to formula-fed neonates. Our study demonstrated that neonates with OFC, especially with high cleft severity, are characterized by markedly increased inflammatory mediators in tongue smear samples within the first weeks of life potentially presenting a risk for oral inflammatory diseases. Therefore, an inflammatory monitoring of neonates with (severe) OFC and the encouragement of mother to breast-milk (bottle) feed might be advisable after birth and/or prior to cleft surgery.
CRIS-Team Scopus Importer:2022-12-16
Keywords: cleft lip and palate; cytokines; mucosal homeostasis; mucosal immunity; neonates; oral; oral inflammation; orofacial clefts

The comparison of the morphology of the mid-palatal suture between edentulous individuals and dentate jaws shows morphological differences - Willershausen, Ines; Krautkremer, Franziska; Hilbert, Tobias; Seidel, Corinna Lesley; Geppert, Carol-Immanuel; Ghanaati, Shahram; Necker, Fabian; Paulsen, Friedrich; Gölz, Lina; Scholz, Michael (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: A profound understanding of the evolution and anatomy of the viscero- and neurocranium is quintessentially important for orthodontists. This particularly alludes to structures, which are directly targeted by orthodontic therapy such as the maxilla and the mid-palatal suture. The anatomy of the mid-palatal suture of toothed individuals is well described, whereas little is known about sutures’ morphological changes after tooth loss. Therefore, the aim of this study was to evaluate the edentulous mid-palatal suture by means of histologic and histomorphometric analysis. Methods: Ten mid-palatal sutures of edentulous donors as well as six age- and sex matched dentulous controls were examined. For the histological and histomorphometric analysis (sutural width, obliteration, vascularization and interdigitation) conventional staining protocols (HE, Movat-Pentachrome, Sirius Red) and immunofluorescence (vWF, TRAP) were performed. Histomorphometric analysis was carried out using NIS-elements imaging software. Results: When compared to dentulous controls, the edentulous investigation group showed a decreased vascularization and sutural width as well as an increased sutural obliteration. Notably, a high variability and inhomogeneity within regard the histomorphometric parameters was seen in edentulous samples. Conclusions: The mid-palatal suture of edentulous individuals showed significant morphological differences compared to individuals with toothed jaws. The loss of teeth and thereby functional loading seems to have a considerable impact on sutures’ morphology.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Atrophy; Edentulous jaw; Histomorphometry; Mid-palatal suture